Nature and antecedents of organizational commitment : considerations for human resource management - Velando Rodriguez, Elena (2015)
Organizational commitment - a central goal for human resources management - has received considerable attention from managers and comportamental researchers. Obtaining elevated levels of employee commitment towards his/her organization requires management strategies that recognize its multidimensional nature and related variables. This research is particularly justified by the need to render the concept of organizational commitment operational through the identification of behaviours and attitudes that have a significant impact upon performance and organizational efficiency. To this end, we have set out the components that make up organizational commitment, its nature and its antecedents, and we have examined potential implications for human resources management. Given the generally accepted connection between organizational commitment and the results/behaviours of a business, it was possible to reach relevant conclusions and illustrate several actions and specific strategies that can extend the scope for human resources management action in regard to organizational commitment.